Estado forestal del Pinus caribaea Morelet var. Hondurensis en el Pinal, Laguna de Perlas, RAAS - López, Javier (Universidad Nacional Agraria, 2004)
The present study was carried out in the strip of land coastbr /between Pearls Lagoon community and the Caribbean sea, in the nearness of Pinar lagoon, 25 km to the north of Bluefields. The geographical coordinates of the area are 12° 13' N and 83° 42' west. The climate presents an annual rainfall of 4 250 mm, an average temperature of 26 °C and a relative humidity of 89 %. The topography is plain and the elevation oscillates between 0-10 masl. The main objective of the study was to evaluate the forest conditions in which forest of P. Caribaea var. hondurensis called the Pinal are found. The methodology employed consisted of gathering all information using air photographs and topographical maps to defined the area and stands group (designed A, B, C,D, E, F and G). Two block and seven stands were found, in which inventory lines with sample plots of 500 m2 each one were employed to measure the individuals with DBH over 10 cm. The intensity it shows is of 1.5% and was measured diameter, height, age and other. In this forest there where found seven stands with a total area covered with pine of 312.42 has. The average age is 23 years and estimated total volume of 97.4 m³ of wood. The density is of 60.61 trees hectare, with an average volume of 13.02 m³ /has and a commercial volume of 8.29 m³ / has. Where found Indices of place 12 (stands G), 9 y 6. Besides, the 63.64 % of the trees has a satisfactory tendency of growth (quality 1 and 2). It can be concluded that the resource is in badly state due to intensive exploitations and annual fires; is a young forest (23 years old), dominated by individuals of small diameters (10-25 cm) and medium height (5-25 m); the available areas or with possibilities of being planting are estimated in 468.64 has. This forest has a half annual increment of 1.43 cm/year, which is considered excellent and is classified with Class P-III, FAO Classification by forests stratification.